Mechanical behavior and microstructure of porous needle: Aluminum borate (Al18B4O33) and Al2O3-Al18B4O33 composites - Hernández, María Florencia (2017)
In this article we assess and compare the complex mechanical behavior of two complex microstructure ceramics material formed within the reaction sintering framework Two comparable pairs of materials with respectively similar microstructures were obtained by reaction sintering from boric acid and alumina. Two single phase porous ceramics were compared with two composite (1:1) porous ceramic. The first and second phases were aluminum borate needles (Al18B4O33) and alumina (Al2O3). The four with comparable grain size and analogous apparent porosities: in diameter (≈ 0.7 μm) and in volume fraction (≈ 45%). The mechanical behavior was studied by means of the diametral compression test at low displacement rate and explained in terms of the texture, microstructure features evaluated by mercury intrusion porosimetry and scanning electron microscopy. Single Al18B4O33 phase porous materials presented higher mechanical strengths than the composite materials. Within the respective microstructural configurations the whisker thickness did not affect significantly the mechanical behavior and parameters. A well-defined fragile behavior was observed and described in the composite material. On the other hand the single Al18B4O33 needle porous material presented a distinctive behavior with local discontinuities without loss of integrity in the diametral stress behavior, and achieved strength up to 50% higher than the corresponding composite.